2006
DOI: 10.1074/jbc.m608272200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants for G Protein βγ Modulation of Ionotropic Glycine Receptors

Abstract: The ligand-gated ion channel superfamily plays a critical role in neuronal excitability. The functions of glycine receptor (GlyR) and nicotinic acetylcholine receptor are modulated by G protein ␤␥ subunits. The molecular determinants for this functional modulation, however, are still unknown. Studying mutant receptors, we identified two basic amino acid motifs within the large intracellular loop of the GlyR ␣ 1 subunit that are critical for binding and functional modulation by G␤␥. Mutations within these seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
83
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 42 publications
(52 reference statements)
7
83
0
1
Order By: Relevance
“…1C). The corresponding wild-type sequence contains a basic motif involved in surface integration and G-protein ␤␥ binding (Sadtler et al, 2003;Yevenes et al, 2006). As evident from human hyperekplexia mutations, the cytosolic arginine residues flanking transmembrane regions 2 and 4 are important for GlyR biogenensis and channel function (Langosch et al, 1993;Rea et al, 2002).…”
Section: Frame-shift Positions Within Tm3-tm4 Loop Harbor Functionallmentioning
confidence: 99%
See 1 more Smart Citation
“…1C). The corresponding wild-type sequence contains a basic motif involved in surface integration and G-protein ␤␥ binding (Sadtler et al, 2003;Yevenes et al, 2006). As evident from human hyperekplexia mutations, the cytosolic arginine residues flanking transmembrane regions 2 and 4 are important for GlyR biogenensis and channel function (Langosch et al, 1993;Rea et al, 2002).…”
Section: Frame-shift Positions Within Tm3-tm4 Loop Harbor Functionallmentioning
confidence: 99%
“…Members of this superfamily share an Ig-like fold of the N terminus and four transmembrane domains (TMs), with TM2 lining the ion pore. Within the intracellular TM3-TM4 loop, a basic motif was identified mediating accumulation of receptors at the cell surface (Sadtler et al, 2003;Yevenes et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The IL is relevant for GlyR function because it was reported that it can be modulated by activation of intracellular cAMP-dependent protein kinase and protein kinase C (Aguayo et al, 1996;Tapia et al, 1997). GlyR modulation and the direct interaction with specific intracellular domains in the receptor have been recently documented (Yevenes et al, 2003(Yevenes et al, , 2006. Furthermore, recent studies showed that, similar to nicotinic acetylcholine receptor (Fischer et al, 2005), the GlyR function can be directly modulated by G␤␥.…”
mentioning
confidence: 99%
“…In the case of GlyRs, mutations in basic amino acids in the IL decreased both the interaction and modulation of G␤␥ with GlyRs (Yevenes et al, 2006). Therefore, using biochemical, electrophysiological, and in silico techniques, we decided to examine the ability of several regions of the ␣ 1 GlyR IL to directly interfere with G␤␥ signaling.…”
mentioning
confidence: 99%
“…By interaction with the dynein complex, gephyrin finally mediates vesicular retrograde transport of the receptor along microtubules (12). For the TM3-4 loops of GlyR␣ subunits, a number of protein-protein interactions that are guided by consensus motifs have been described (13,14). However, the roles of these interactions and consensus motifs in trafficking of the receptor remain elusive.…”
mentioning
confidence: 99%